The Effect of Heating and Cooling Media Temperature on Injection Molding Products Shrinkage - Gumono Gumono; Zahratul Jannah AR; Agus Sujatmiko; Candra Adityaca (Asian Journal Science and Engineering, 2022)
Injection molding is the process of molding products with various shapes and sizes from plastic materials. The problem that often arises is the presence of product defects due to shrinkage. In this regard, the effect of water cooling on product size shrinkage in the injection molding process of making acetabular cups with polypropylene plastic and metal steel mold materials will be investigated through experimental investigations. The test begins with the manufacture of molds and injection machines, then the PP liquid plastic is injected twice into the mold, the first with cooling and the second without cooling. Both products are compared for depreciation by measurement. Shrinkage analysis is done by measuring the height and diameter of the product which is then compared with the size of the mold, so that final conclusions can be drawn. Measurement of shrinkage on the outside of the product is taken from three directions, namely the height of the X-axis product (dx), the outside diameter of the Y-axis product (dy), and the outside diameter of the Z-axis product (hz). For the inside of the product with a hemispherical shape, the shrinkage measurement is calculated by calculating the volume which can then be found the average radius. The results showed that the average shrinkage of the cooling test on the X axis = 1.224 %, on the Y axis = 1.857 %, on the Z axis = 1.83%, and on the radius r = 0.825 %. The average shrinkage of the test without cooling on the X axis = 1,591 %, on the Y axis = 2,32%, on the Z axis = 2,369 %, and on the radius r = 1,267 %. Keywords: Injection Molding, Shrinkage, Heating Cooling Temperature